2018
DOI: 10.1371/journal.pone.0196634
|View full text |Cite
|
Sign up to set email alerts
|

Growth differentiation factor-15 and fibroblast growth factor-23 are associated with mortality in type 2 diabetes – An observational follow-up study

Abstract: ObjectivesTwo biomarkers, growth differentiation factor 15 (GDF-15) and fibroblast growth factor 23 (FGF-23)), reflecting different aspects of renal pathophysiology, were evaluated as determinants of decline in estimated glomerular filtration rate (eGFR), incident cardiovascular disease (CVD) and all-cause mortality in patients with type 2 diabetes (T2D) and microalbuminuria, but without clinical cardiac disease.Materials and methodsProspective study including 200 T2D patients. The predefined endpoint of chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…The main finding of our study is that plasma FGF23 levels are independently associated with mortality and MACE in patients with type 2 diabetes and normal or mildly impaired kidney function. This observation extends previous studies in CKD patients and patients with type 2 diabetes (1,(8)(9)(10). Interestingly, the associations in our study restricted to patients with an eGFR $60 mL/min/1.73 m 2 persisted after adjustment for eGFR, linking a higher FGF23 level with adverse outcomes even in patients without impaired kidney function.…”
Section: Discussionsupporting
confidence: 89%
“…The main finding of our study is that plasma FGF23 levels are independently associated with mortality and MACE in patients with type 2 diabetes and normal or mildly impaired kidney function. This observation extends previous studies in CKD patients and patients with type 2 diabetes (1,(8)(9)(10). Interestingly, the associations in our study restricted to patients with an eGFR $60 mL/min/1.73 m 2 persisted after adjustment for eGFR, linking a higher FGF23 level with adverse outcomes even in patients without impaired kidney function.…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with the findings from our study that showed that the duration of diabetes morbidity, HbA1c, CRP, and systolic blood pressure was a risk factor for DR in patients with type 2 diabetes. In line with a previous study ( 28 ), we also found that the plasma levels of GDF-15 were significantly associated with renal damage and could predict the development of diabetic retinopathy in patients with type 2 diabetes. Importantly, the association between circulating plasma GDF-15 concentrations and the progression of DR in type 2 diabetic patients in our study was independent of the traditional DR risk factors mentioned above.…”
Section: Discussionsupporting
confidence: 92%
“…Higher levels of circulating GDF-15 have been linked to an increased risk for several adverse outcomes, including a recent study showing an association with incident type 2 diabetes (27), deteriorating microalbuminuria (28), progression of albuminuria in persons with type 2 diabetes (28), kidney function decline and cardiovascular risk in persons with type 1 diabetes (29), early death in patients undergoing haemodialysis (30), as well as incident heart failure and cardiovascular events in the general population (31). The fact that GDF-15 was the only biomarker that was associated with incident cardiovascular events is interesting and also supported by several studies showing associations between GDF-15 levels and both cardiovascular morbidity and mortality (32)(33)(34)(35).…”
Section: Gdf-15mentioning
confidence: 89%